2016
DOI: 10.1016/j.athoracsur.2016.04.007
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Deep Versus Moderate Hypothermia on Postoperative Kidney Function After Elective Aortic Hemiarch Repair

Abstract: We applied the sensitive RIFLE criteria to examine AKI in patients undergoing elective aortic hemiarch replacement for aneurysmal disease. Baseline renal dysfunction, lower ejection fraction, and longer CPB time are independent predictors of AKI. Compared with DHCA/RCP, our data suggest that an MHCA/ACP cerebral protection strategy does not appear to be associated with worse postoperative renal outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 26 publications
5
49
0
Order By: Relevance
“…Moderate hypothermic circulatory arrest with antegrade cerebral perfusion during complex aortic surgery has been embraced by an increasing number of surgical groups, with data suggesting that this is not associated with an increased AKI risk . Conversely, hyperthermic perfusion during CPB, defined as a cumulative time at >37°C, is associated with an increase in AKI incidence .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moderate hypothermic circulatory arrest with antegrade cerebral perfusion during complex aortic surgery has been embraced by an increasing number of surgical groups, with data suggesting that this is not associated with an increased AKI risk . Conversely, hyperthermic perfusion during CPB, defined as a cumulative time at >37°C, is associated with an increase in AKI incidence .…”
Section: Resultsmentioning
confidence: 99%
“…175,176 Moderate hypothermic circulatory arrest with antegrade cerebral perfusion during complex aortic surgery has been embraced by an increasing number of surgical groups, with data suggesting that this is not associated with an increased AKI risk. 177 Conversely, hyperthermic perfusion during CPB, defined as a cumulative time at >37°C, is associated with an increase in AKI incidence. 178 In a study achieving clinical equipoise through propensity score matching, duration of hyperthermic perfusion was independently associated with severity of AKI, with a 51% increase in the incidence for every 10 minutes of hyperthermic perfusion.…”
Section: Nonpharmacological Strategiesmentioning
confidence: 99%
“…In cases where a hemiarch or total arch replacement was carried out in the index operation, the current operation will involve a reoperative hemiarch or a total arch replacement. In both circumstances, patients are cooled to isoelectric EEG silence and either retrograde cerebral perfusion is utilized for hemiarch replacements and antegrade cerebral perfusion is utilized for total arch replacements . In these circumstances, all graft tissue is excised and all Teflon felt material is removed from the arch to eliminate all infection and reduce the risk of reinfection.…”
Section: Managementmentioning
confidence: 99%
“…A retrospective study by Arnaoutakis et al found that MHCA was not associated with worse renal outcomes. 108 Another retrospective study by Numata et al found similar mortality and PND with arrest above and below 28°C but significantly reduced rates of postoperative renal failure requiring dialysis and postoperative respiratory failure with prolonged ventilation in patients with arrest temperatures more than 28°C. 109 Other studies have demonstrated safety and promising outcomes for MHCA with regard to mortality, neurologic injury, dialysis-dependent renal failure, CPB times, neurologic injury, and serum ischemic markers.…”
Section: Mild-to-moderate Hypothermiamentioning
confidence: 92%